RFID Based Smart Health Card for Managing Patients Medical Records - Amat Bakir, Mohammad Ramdan; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2023)
Smart cards are an efficient and safe solution to store medical information. Smart cards, on the other hand, give immediate access to medical information, protect medical privacy, and provide regulated access to data. They are also compatible with all Medical Information Systems, networks, and apps. The innovation of this smart e-health card is to store digital data every time an appointment is constructed by the patient and doctor. It is equipped with Arduino Uno, Arduino Ethernet Shield, and RFID reader with a tag and card. The implementation of this system only requires the user to scan the card and the digital data will be stored in the system. Traditional data collection such as filling out a form are taking longer time and is not effective. The forms also can be misplaced and a lot of time is required to find the data of a person. With RFID technology, this issue can be solved as it only required users to scan, therefore, the digital data of the patients will be stored in the system.